Diagnostic and management practices for phenylketonuria in 19 countries of the South and Eastern European Region: survey results - Giżewska, Maria; MacDonald, Anita; Bélanger-Quintana, Amaya; Burlina, Alberto; Cleary, Maureen; Coşkun, Turgay; Feillet, François; Muntau, Ania C.; Trefz, Friedrich K.; van Spronsen, Francjan J.; Blau, Nenad (European journal of pediatrics, 2016)
To avoid potentially severe outcomes, phenylketonuria (PKU) must be detected as soon as possible after birth and managed with life-long treatment. A questionnaire-based survey was performed to document diagnosis and management practices for PKU in a region of Southern and Eastern Europe. Prevalence and management data were obtained from 37/59 (63 %) centres within 19/22 (86 %) contacted countries (N = 8600 patients). The main results’ analysis was based on completed questionnaires obtained from 31 centres (53 %) within 15 countries (68 %). A median of 10 % of patients per centre had been diagnosed after the newborn period. Metabolic dieticians and specialised adult PKU clinics were lacking in 36 and 84 % of centres, respectively. In 26 % of centres, treatment initiation was delayed until >15 days of life. Blood phenylalanine (Phe) thresholds to start treatment and upper Phe targets were inconsistent across centres. Ten percent of centres reported monitoring Phe every 2 weeks for pregnant women with PKU, which is insufficient to minimise risk of neonatal sequalae. Sapropterin dihydrochloride treatment was available in 48 % of centres, with 24-h responsiveness tests most common (36 %). Only one centre among the five countries lacking newborn screening provided a completed questionnaire., Conclusion: Targeted efforts by health care professionals and governments are needed to optimise diagnostic and management approaches for PKU in Southern and Eastern Europe.“What is Known”• PKU must be detected early and optimally managed throughout life to avoid poor outcomes, yet newborn screening is not universal and diagnostic and management practices for PKU are known to vary widely between different centres and countries. - • Targeted efforts by health care professionals and governments are needed to optimise diagnostic and management approaches. - “What is New”• PKU management practices are documented in 19 South and Eastern European countries indicating a heterogeneous situation across the region. - • Key areas for improvement identified in surveyed centres include a need for comprehensive screening in all countries, increased number of metabolic dietitians and specialised adult PKU clinics, delayed time to treatment initiation, appropriate Phe thresholds, Phe targets and monitoring frequencies, and universal access to currently available treatment options.
Published online: 8 September 2015
Gesehen am 16.06.2020